Evaluation of Incisor Inclination on Smile on Lateral Profile - Mhatre, Tejas Chandrakant; Phaphe, Sandesh Ashok; Patankar, Rutika Chandrakant; Ganiger, Chanamallappa Ramappa; Pawar, Renuka Lalit; Ahammed, Yusuf; Mane, Pratap Nivrutti (Journal of Orofacial Research, 2018)
Background: Smile is the key that fits the lock of every heart. Objective: The aim of the study was to evaluate inclination of maxillary incisors on smile aesthetics in relation with the profile view and to evaluate the perception and awareness of dentists, orthodontists, lay people and students towards smile attractiveness. Methods: A right smiling lateral profile photographs of a 21-year-old female subject were taken and then altered. Five final images were obtained which were printed separately and randomly distributed to four groups of evaluators (50 orthodontists, 50 dentists, 50 lay people and 50 students). A Visual Analogue Scale (VAS) was distributed to them for judgment. The obtained data were subjected to statistical analysis using ANOVA and Fischer’s test. Results: The results showed significant variation in the perception of smile based on the incisor inclination among different professionals (Wilk’s Lambda, F = 2.825, P = <0.001). The original profile smile had the highest score among all professions (58% of dentists, 94% of orthodontists, 36% of students and 28% of layman). Conclusion: Orthodontists preferred inclination labially; dentists and laypeople did not appreciate excessive incisor inclination in either the lingual or the labial directions.